Internet connectivity disruption in Croatia (Croatia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Croatia. Data sourced from IODA.
Network Disruption Incident ID: HR-2026-0001. Severity: critical. Confidence: 67%